A FAVE Cache Strategy for Producer Mobility in Content Centric Networks - Dr.Nedunchezhian T, Dr.Korla Swaroopa, Dr.S. Kalai Magal (International Journal of Advanced Science and Technology, 2020)
Content centric network is a Future internet architecture where a network uses purely content names along with prefixes as an addressing system instead of using internet protocol addresses of the hosts to refer the content. In CCN various solutions are proposed by researchers to support the mobility of consumers and providers. Consumer mobility is usually easy to solve because of naturally retransmission of the unreliable interests. But the provider mobility is hard to deal due to reason of continuous location change of a node that really provides the content. So every time when location changing the retrieved Content should effect with delayed performance. In this paper we proposed a scheme called “A FAVE Cache Strategy for producer mobility in content centric networks”.Always allow consumers to receive the entire content before node leaves the region. For this we considered attached content routers which are available within one hop distance and also the content is to be cached based on popularity of content. In this approach of content provider mobility addressing we deal with two different directions which are“where to cache the content” and “how frequently we are getting the interests with that prefixes at that selective neighbors”. Finally, we evaluate the performance withour proposedfavorite selected neighbors caching scheme.